Extrusion encapsulation of Lactobacillus bulgaricus coated by carrageenan – alginate with additional tofu waste flour prebiotic - Muhardina, Vina; Meutia Sari, Putri; Aisyah, Yuliani; Haryani, Sri; Atul Mega, Fitrah (International Journal of Engineering and Technology, 2019)
Survival phase of probiotic Lactobacillus bulgaricus, depends on its living conditions, which are processing stages, storage condition and acidity level in digestive tract. The severity states of environment and improper treatment may cause a reduction of probiotic viability in food products. Extrusion method was used to encapsulate the bacteria by using combination of encapsulating agents and a certain percentage of prebiotic in order to enhance the viability of probiotic in acid and cold condition. This study used two factors, which were capsule agents (alginate and carrageenan), and percentages of tofu waste flour (1.5%, 2%, 2.5%, and 3%). The results showed that carrageenan was better in protecting probiotics at pH 2 with a total LAB of 4.23 LogCFU/gram, 42.5% viability of LAB and 41% efficiency encapsulation compared to alginate 3.92 LogCFU/gram, 38.2% viability and 37.9% efficiency encapsulation. The addition of tofu waste flour causes an increase in the growth of probiotic bacteria up to 10.5 LogCFU/gram. In the simulation conditions of gastric acid (pH 2), the combination of the use of carrageenan with the optimal percentage of tofu waste flour (3%) results in the most effective encapsulation conditions for probiotic viability and the highest yield of encapsulation.Â